Student Character Building through Project Based Learning in the CCU (Cross Cultural Understanding) Course - Andika, Alek; Heriyanto, Dwi (International Proceedings of Nusantara Raya, 2024)
This research explores how student character is formed through Project-Based Learning (PjBL) through the Cross Cultural Understanding (CCU) course. PJBL offers students the opportunity to address real-life challenges and problems. In addition, PjBL also encourages a more dynamic classroom approach. This research used a qualitative research design. This research shows that the PjBL method is in line with the concept of 21st-century learning, namely in developing student character, including critical thinking, creativity, communicative and collaborative. In general, PjBL provides a different set of skills than those usually obtained in traditional teaching and learning, making it a viable learning model for shaping student character so they can face new lives in the challenges of society 5.0. Studying the effect of project-based learning on student character development within the CCU framework in Indonesia is a significant topic of research. Learning is a complex journey that extends beyond just acquiring academic knowledge, and the growth of students' personality, principles, and cultural understanding is equally significant. This research involved 25 individuals, including students and lecturers, selected through random sampling. Data collection includes interviews, classroom observations, and document analysis. The research results show three main things in cultivating student character: strengthening communication skills, teamwork and understanding related to moral values in CCU. This study provides valuable information for lecturers and policymakers to improve the quality of education. Including PJBL in CCU is a promising approach to prepare students for the complexities of a globalized society like Indonesia and other culturally varied countries.